Le lettré chinois : designer ignoré des traductions - Émilie Bonnard (Appareil)
The view of Western on China is constantly changing, depending on the exchanges between the two areas and the emotions that embrace the protagonists. Initially, the increase in exchanges mainly favored the translation of Western texts into Chinese writing. Later, the growing attraction to Chinese culture has led to an increase in the number of sinologists and the diversification of translations of Chinese texts in the Western world. The translation of the stories concerning the creation, before 1911 and the advent of the Republic, revealed the complex personality of the scholar who is probably not limited to his position as an administrative official. He appears as an artist and intellectual, an ingenious scientist, sometimes a gardener (Ji Chen) or a botanist (Chen Haozi), or even an inventor (Li Yu). The stories, marginal according to the translators, of these creative and inventive men, at the crossroads of disciplines, nevertheless echo the stories of contemporary designers. The translation of Chinese literary stories into French language that we studied, tell a particularly refined art of living with perfume. The scholars conceived utensils, uses, circumstances, to live harmoniously in a fragrant world. Today, in these translations, should we qualify this character as “scholar”, “designer”, or even more precisely “olfactory designer”? A dialogue between sinologists and designers seems to be essential.